Architectures of Nigeria : architectures of the Hausa and Yoruba peoples and of the many people between--tradition and modernization - Carroll, Kevin, 1920-1993. (London : Ethnographica ; [Cork] : Society of African Missions ; [S.l.] : Lester Crook Academic Pub., 1992)
This work describes the traditional architectures of the western half of Nigeria, covering the huge area from the Hausa people of the north to the Yoruba people of the south.
Includes bibliographical references (p. 121-122) and index.
Keywords: Architecture -- Nigeria; Domestic architecture. Houses. Dwellings; Vernacular architecture -- Nigeria